2014
DOI: 10.1007/s10803-014-2321-5
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder Profile in Neurofibromatosis Type I

Abstract: Neurofibromatosis Type 1 (NF1) is a common autosomal dominant single-gene disorder, in which the co-occurrence of autism spectrum disorder (ASD) has attracted considerable research interest recently with prevalence estimates of 21-40%. However, detailed characterization of the ASD behavioral phenotype in NF1 is still lacking. This study characterized the phenotypic profile of ASD symptomatology presenting in 4-16 year old children with NF1 (n = 36) using evidence from parent-rated Social Responsiveness Scale a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 40 publications
7
56
1
1
Order By: Relevance
“…Our phenotype analyses suggested additional similarities with idiopathic ASDs, such as a male-biased sex ratio. Other groups have performed independent studies with highly consistent findings[5762]. Studying multiple disorders in the same biological pathway could therefore both increase the power of our study and increase the likelihood of results translating to an even broader diagnostic category, idiopathic ASDs.…”
Section: Introductionsupporting
confidence: 53%
“…Our phenotype analyses suggested additional similarities with idiopathic ASDs, such as a male-biased sex ratio. Other groups have performed independent studies with highly consistent findings[5762]. Studying multiple disorders in the same biological pathway could therefore both increase the power of our study and increase the likelihood of results translating to an even broader diagnostic category, idiopathic ASDs.…”
Section: Introductionsupporting
confidence: 53%
“…Indeed, in recently published pathway network analyses and sequencing studies, overlap was found for several ASD candidate genes and cancer [30, 112]. Correspondingly, germline mutations in NF1, which cause neurofibromatosis type I, often display autistic-like behaviors [113, 114]. The molecular genetic overlap suggests that some novel cancer therapies currently being developed, especially those that target the epigenome might be beneficial in treating subgroups of individuals with neurodevelopmental disorders [112, 115].…”
Section: Discussionmentioning
confidence: 99%
“…However, earlier reports 8,13 on subsets of this cohort demonstrated no association between QAT burden and NF1 severity, and we recapitulate the independence of QAT ratings from measurement of IQ as similarly seen in idiopathic ASD. 3840 Although deficits in reciprocal social behavior have been demonstrated 41,42 to be genetically independent from non-ADHD domains of psychopathology, significant elevations have been observed in patients with anxiety disorder. To this end, the lack of general psychopathology data in this cohort limits a comprehensive characterization of the NF1-ASD phenotype and should be a focus of future research.…”
Section: Discussionmentioning
confidence: 99%